2013
DOI: 10.3109/10428194.2012.726721
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-10 in the regulation of tumorigenicity of a T cell lymphoma

Abstract: Interleukin-10 (IL-10) is a cytokine that is produced by a variety of immune cells and is known to inhibit T helper cell type 1 (TH1) responses, which are essential to combat tumors. In the present study, we used LSA, a T cell lymphoma cell line that expresses IL-10, to study the role of this cytokine in its tumorigenesis. To this end, LSA cells were modified to overexpress IL-10 or to block its expression via Ret-off-IL-10 vector transfection. Interestingly, blocking IL-10 expression using Ret-off-IL-10 antis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…These data demonstrated that Nrp-1 inhibited CD8a + protein expression in tumor tissues and limited its function (CD8 + IFN-γ + ). The mouse spleen-derived DC (spDC) activation and maturation status were assessed using flow cytometry 23 . Significantly more mature CD11b + CD11c hi (mDC) cells were detected in IL-10 knockout tumor-bearing mice compared with WT mice (mDC, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data demonstrated that Nrp-1 inhibited CD8a + protein expression in tumor tissues and limited its function (CD8 + IFN-γ + ). The mouse spleen-derived DC (spDC) activation and maturation status were assessed using flow cytometry 23 . Significantly more mature CD11b + CD11c hi (mDC) cells were detected in IL-10 knockout tumor-bearing mice compared with WT mice (mDC, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mona R. Hassuneh et al used LSA (a T-cell lymphoma cell line expressing IL-10) to study the role of IL-10 in tumorigenesis. Interestingly, the administration of anti-IL-10 antibodies significantly inhibited the growth of tumors in LSA ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since TGF␤1 can induce regulatory T-cells (Tregs), which make IL-10, this particular anti-inflammatory action of TGF␤1 is most likely mediated through the induction of Tregs in vivo [70,71]. Interleukin (IL)-10 has anti-inflammatory properties that is encoded by the IL-10 gene in humans [72]. IL-10 blocks NF-B activation, enhances B cell survival, proliferation, antibody production, and furthermore, it can regulates the JAK-STAT signaling pathway [73,74].…”
Section: Tgfˇ1 and Il-10 Signalingmentioning
confidence: 99%